Research Oon Spatial Planning Strategy From the Perspective of Circular Economy - Ling, Wanyun (International Journal of Natural Resources and Environmental Studies, 2024)
Under the situation of the increasing shortage of global resources and the deterioration of the environment, circular economy, as a potential countermeasure, has gradually emerged as a key path to ensure the sustainable evolution of social economy. This study chooses the field of architecture as the starting point to analyze the application and improvement of spatial planning strategy from the perspective of circulation, hoping to realize the efficient closed loop utilization of resources. At the beginning of this paper, we summarized the essential characteristics of circular economy and its embodiment in the construction industry, and further studied the exemplary practice of circular economy in the European construction field, including policy support, demonstration projects and major obstacles faced. Then through the empirical investigation of the current situation of circular economy in China’s construction industry, and compared with the examples in Eurasia, we explain the differences between China and the United States in this field and the causes. On the basis of these analyses, we construct a theoretical framework of spatial planning based on the concept of circular economy, design targeted tactics for different architectural schemes, and study the dynamic mechanism to ensure that the strategy takes root. Empirical evidence shows that accurate and adaptable spatial planning is tantamount to a significant improvement in the resource utilization of the construction industry, and also provides a strong support for regional and even national sustainable vision. Finally, we look forward to the future research blueprint, emphasizing the strengthening of international cooperation and dialogue to jointly meet the global difficulties, in order to accelerate the ecological and low-carbon transformation of the construction industry.